2019
DOI: 10.1016/j.crci.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric oxidation of acetophenone derivatives and benzophenone in acetonitrile on a platinum and glassy carbon electrode

Abstract: Full paper/M emoire Voltammetric oxidation of acetophenone derivatives and benzophenone in acetonitrile on a platinum and glassy carbon electrode L aszl o Kiss a, b, * , S andor Kuns agi-M at e a, b, c

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…This compound might be adsorbed on the glassy carbon surface and further oxidized on the aromatic ring, resulting in the formation of polymers. The benzoyl moiety can also react as it was demonstrated in an earlier work in the case of benzophenone: an anodic peak appeared in the first scan with the glassy carbon electrode [8]. It evidences unambiguously that in the previous studies with 3,4dihydroxybenzaldehyde, oxidation of the formyl group took place where the second peak appeared and where the second smaller peak showed up by the monohydroxy derivatives.…”
Section: Complementary Experiments With Benzaldehydesupporting
confidence: 80%
See 1 more Smart Citation
“…This compound might be adsorbed on the glassy carbon surface and further oxidized on the aromatic ring, resulting in the formation of polymers. The benzoyl moiety can also react as it was demonstrated in an earlier work in the case of benzophenone: an anodic peak appeared in the first scan with the glassy carbon electrode [8]. It evidences unambiguously that in the previous studies with 3,4dihydroxybenzaldehyde, oxidation of the formyl group took place where the second peak appeared and where the second smaller peak showed up by the monohydroxy derivatives.…”
Section: Complementary Experiments With Benzaldehydesupporting
confidence: 80%
“…As can be seen, the electrode was passivated quickly by derivatives containing only one hydroxy group. In an earlier work where para-substituted acetophenones and among them, 4 0 -hydroxyacetophenone was investigated in acetonitrile at higher anodic potentials, passivation took place continuously by repeating the scans [8]. In that work, it was demonstrated that the solvent itself contributed to the process.…”
Section: Investigation Of the Hydroxybenzaldehydes On A Glassy Carbon...mentioning
confidence: 99%
“…The potential window was between 0 and 2 V for p-methoxyphenol as its oxidation peak appeared at less positive potential than 2 V. It shows that the methoxy group significantly activates the benzene ring. Its voltammograms were reproducible, however the height of the first one is a little smaller than that of the other ones indicating that the surface of platinum was cleaned electrochemically in the first scan which was also observed by other electroactive materials in acetonitrile on platinum electrode [17]. As a matter of fact p-methoxyphenol is the monomethyl ether of 1,4-dihydroxybenzene which can be oxidized similarly to 1,4-dihydroxybenzene producing a protonated species similar to p-benzoquinone in aprotic nonaqueous solvents.…”
Section: Studies With the Para-substituted Phenols In Acetonitrilementioning
confidence: 64%
“…In an earlier work where substituted acetophenones were examined in acetonitrile between 0 and 4 V it was found that the oxidation peaks of acetophenones appeared only in the first scan due to the solvent [17]. By increasing the electrode potential to extreme values might result in undesired reactions which take place at the electrode/solution interface being due to the diminished solvent and/or electrode stability.…”
Section: Extension Of the Potential Window To 3 Vmentioning
confidence: 99%
“…Merece realçar que uma ampla diversidade de eletrodos de trabalho tem sido aplicada nas pesquisas sobre o comportamento eletroquímico de nitro-heterocíclicos, a se destacar eletrodos sólidos como ouro, platina ou carbono. O emprego destes eletrodos é justificado pelos intervalos de potenciais úteis de trabalho que apresentam em diversos solventes (CHIAVASSA, CAMILO, LA-SCALEA, 2021;JASHARI et al, 2021;ABBAR, METI, NADIBEWOOR, 2020;KISS, KUNSÁGI-MÁTÉ, 2019;STOILJKOVIC et al, 2012).…”
Section: íNdiceunclassified